The impact of Search Volume Index on FDI outflow: the moderating role of uncertainty avoidance - Mammadrzayev, Vusal; Nadirov, Orkhan; Pavelková, Drahomíra (Journal of Business Economics and Management, 2025)
This study examines the relationship between the Search Volume Index (SVI) and FDI outflow levels and tests whether the level of national culture, particularly whether the Uncertainty Avoidance Index (UAI), moderates such a relationship. The authors document that SVI is positively associated with FDI outflow in the sample of 69 countries. When we distinguish between low and high-uncertainty avoidance countries, we find that this positive association is significant at the current value of SVI for countries with low uncertainty avoidance. However, the relationship becomes stronger for countries with high uncertainty avoidance at the one-year time lag of SVI. Moreover, the results remain intact after various robustness checks. These results imply that the level of national culture may cause individuals to hesitate to invest through internet search queries. Our empirical findings should be particularly informative for investors from countries whose governments exhibit high levels of uncertainty avoidance, as they spend more time on investment planning than investors from countries whose governments exhibit low uncertainty avoidance.